Import Substitution of Combination Wire Rope-Part IV A Guide-line for Standardisation of Combination Ropes - B., Meenakumari; P.A., Panicker (Fishery Technology, 2025)
Consolidating and computing the observations and results of earlier works, 192 spe- clfications of combination ropes were worked out as a guideline for standardisation. The combination ropes are basically ofsix strand construction with steel/fibre core. The core is either 6 (6/1) steel wire or 3 stranded PP tape ropes. The rope strands are either with single layer of wires with a fibre core (8/f and 12/f) or with an outer thicker and inner thinner layers of wires of same tensile designation with a fibre core (9/6/f, 12/6/f`, 12/9/f' and 15/9/f). The rope strands are covered with 8 strands of`PP soft twisted tape yarns. Specifications of 96 ropes with ibre and steel wire core separately using wires of' 120, 140 and 160 tensile designation and nominaldiameter ranging between 0.5 and 1.0 mm and computing the rope diameter, mass and breaking load are presented.